2022
DOI: 10.1007/s42452-022-05161-2
|View full text |Cite
|
Sign up to set email alerts
|

Fe2(SO4)3-assisted anaerobic digestion of pig manure: the performance of biogas yield and heavy metal passivation

Abstract: The harmless disposal and recycling treatment technology of livestock manure has received increasing attention in recent years. In this study, Fe2(SO4)3 was added during anaerobic digestion (AD) of pig manure (PM) to investigate the effects of different doses of Fe2(SO4)3 on biogas yield and heavy metal passivation. The results showed that the highest biogas yield was observed after adding a moderate dose of Fe2(SO4)3 (3%, based on the total solids), while the elevated result was inhibited as the Fe2(SO4)3 dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…For example, Yu, et al [159] demonstrated that P fertilizer significantly increased soil pH and available P while decreasing soil available HM concentrations. Additionally, Zhou, et al [160] effectively passivated Cu, Zn, and As by adding 3% Fe 2 (SO 4 ) 3 to pig manure, which led to a decrease of 82.35% and 80.00% in available Cd and Pb concentrations, respectively [161]. Moreover, foliar inhibitors containing Si/Se were found to reduce the available HMs and inhibit the absorption of Cd by plants in red soil [162].…”
Section: Agronomic Measuresmentioning
confidence: 99%
“…For example, Yu, et al [159] demonstrated that P fertilizer significantly increased soil pH and available P while decreasing soil available HM concentrations. Additionally, Zhou, et al [160] effectively passivated Cu, Zn, and As by adding 3% Fe 2 (SO 4 ) 3 to pig manure, which led to a decrease of 82.35% and 80.00% in available Cd and Pb concentrations, respectively [161]. Moreover, foliar inhibitors containing Si/Se were found to reduce the available HMs and inhibit the absorption of Cd by plants in red soil [162].…”
Section: Agronomic Measuresmentioning
confidence: 99%